Implementing patient-reported outcomes in routine clinical care for diverse and underrepresented patients in the United States - Colby J. Hyland; Ruby Guo; Ravi Dhawan; Manraj N. Kaur; Paul A. Bain; Maria O. Edelen; Andrea L. Pusic (SpringerOpen, 2022)
Plain English summary Patient-reported outcomes (PROs) allow doctors and researchers to understand the patient perspective, such as how they are doing physically, mentally, or socially. When used, PROs can improve health and increase satisfaction of patients. Many clinics and hospitals are interested in using PROs in everyday care. Doctors, hospitals, and insurance companies are also using information from PROs to decide if the care they give is good quality. Unfortunately, certain groups of patients, such as racial and ethnic minorities and patients with low income, report worse PROs. Because of these differences, it will be important to make sure that PROs are being collected from all people, but not much is known regarding how this has been done. This study demonstrates what is known so far with regard to using PROs in everyday clinical care for these diverse patient groups. Findings from this study show that PROs can be successfully collected, but more work is needed in certain medical fields, and some types of patients have specific needs, concerns, or preferences with regard to PRO collection.